2017
DOI: 10.1002/aet2.10004
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Relationship Between Emergency Medicine Trainee Burnout and Clinical Performance in a High‐fidelity Simulation Environment

Abstract: Objective: Burnout is prevalent among emergency medicine (EM) physicians, with physicians experiencing burnout more likely to report committing medical errors or delivering suboptimal care. The relationship between physician burnout and identifiable differences in clinical care, however, remains unclear. We examined if EM trainee burnout was associated with differences in clinical performance using high-fidelity simulation as a proxy for patient care. Methods:In this cross-sectional study across six institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
4
14
1
Order By: Relevance
“…Our study's rate of trainee burnout (78%) was higher than prior estimates among EM trainees (55%–65%) . Recent work, however, demonstrates a trend of increasing burnout rates among EPs and trainees, with current estimates between 70 and 75% .…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Our study's rate of trainee burnout (78%) was higher than prior estimates among EM trainees (55%–65%) . Recent work, however, demonstrates a trend of increasing burnout rates among EPs and trainees, with current estimates between 70 and 75% .…”
Section: Discussioncontrasting
confidence: 81%
“…There are many speculated reasons for this phenomenon among all physicians, not just EPs, and our study did not seek to address this issue . Nevertheless our results add to growing literature that suggests an association between physician burnout and negative patient care experiences . Residency programs may need to identify and address trainee burnout not only to enhance the well‐being of individual residents but also to potentially improve the quality of care they provide to patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…7 It is troubling, however, that EM trainees report similarly high levels of burnout as practicing EM attendings. [2][3][4] Coupled with recent evidence demonstrating an association between physician burnout and lower quality of care, 3,8,12 accurate identification and effective methods of addressing physician burnout are paramount.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recent work demonstrated that burnout is prevalent (55%-65%) among EM trainees as early as the second year of training. 3,4,8 Efforts to ameliorate the impact of burnout on trainees have been suggested, although their effectiveness remains unclear. 9 One reason for the uncertain success of these wellness interventions may be due to their implementation among trainees en masse, without discrimination between those with high versus low levels of burnout.…”
mentioning
confidence: 99%